2014
DOI: 10.1152/ajpheart.00821.2013
|View full text |Cite
|
Sign up to set email alerts
|

Apelin gene therapy increases myocardial vascular density and ameliorates diabetic cardiomyopathy via upregulation of sirtuin 3

Abstract: Microvascular insufficiency contributes to cardiac hypertrophy and worsens heart dysfunction in diabetic cardiomyopathy. Our recent study shows that apelin may protect ischemic heart failure via upregulation of sirtuin 3 (Sirt3) and angiogenesis. This study investigated whether apelin promotes angiogenesis and ameliorates diabetic cardiomyopathy via activation of Sirt3. Wild-type (WT) and diabetic db/db mice were administrated with adenovirus-apelin to overexpressing apelin. In WT mice, overexpression of apeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 53 publications
4
74
0
Order By: Relevance
“…Apelin, expressed widely in various organs, including the heart, kidney, lung, brain, skeletal muscles, and gastrointestinal tract, is a multifunctional protein involved in angiogenesis, energy metabolism regulation, and fluid homeostasis [17,18]. Apelin is reported to have a beneficial effect in diabetes and its complications by promoting glucose uptake, improving insulin sensitivity, reducing body adiposity, enhancing brown adipogenesis, controlling diabetes-induced kidney hypertrophia and albuminuria, and suppressing oxidative stress [19][20][21][22]. A clinical study in CKD patients with cardiovascular disease indicated that patients with high serum apelin levels had higher adiponectin levels, greater eGFR, and lower IL-6, resistin, visfatin, and LDL-C levels, with a lower cardiovascular hospitalization and mortality [23].…”
Section: Discussionmentioning
confidence: 99%
“…Apelin, expressed widely in various organs, including the heart, kidney, lung, brain, skeletal muscles, and gastrointestinal tract, is a multifunctional protein involved in angiogenesis, energy metabolism regulation, and fluid homeostasis [17,18]. Apelin is reported to have a beneficial effect in diabetes and its complications by promoting glucose uptake, improving insulin sensitivity, reducing body adiposity, enhancing brown adipogenesis, controlling diabetes-induced kidney hypertrophia and albuminuria, and suppressing oxidative stress [19][20][21][22]. A clinical study in CKD patients with cardiovascular disease indicated that patients with high serum apelin levels had higher adiponectin levels, greater eGFR, and lower IL-6, resistin, visfatin, and LDL-C levels, with a lower cardiovascular hospitalization and mortality [23].…”
Section: Discussionmentioning
confidence: 99%
“…Sirtuin 3 (SIRT 3) is a member of Sirtuin family, the mammalian homologues of the silent information regulator 2 first discovered in Saccharomyces cerevisiae as an NAD+-dependent histone deacetylase [11,12]. The other Surtuin members, especially SIRT1 has been reported to be associated with the clinical features and prognosis of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Apelin treatment abolishes development of cardiac hypertrophy, as well as preventing fibrosis progression and cardiac contractile dysfunction (37). In addition, apelin gene therapy increases myocardial vascular density and ameliorates diabetic cardiomyopathy via upregulation of sirtuin 3 (38). Previous studies demonstrated that apelin treatment contributes to cardioprotection in cardiac I/R injury, as well as angiotensin II-or isoproterenol-induced cardiac remodeling (39,40).…”
Section: Discussionmentioning
confidence: 99%